Analisis Pengadaan Sarana Dan Prasarana Kantor Pada PT XYZ - Topan Topan; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The purpose of this research is to determine the procurement of office facilities and infrastructure at PT XYZ, as well as determine the obstacles in maintaining office facilities and infrastructure. From the results of this research, it can be seen that procurement of office facilities and infrastructure must be carried out regularly so that work can run properly, and employees can work comfortably without any complaints when in the office.